Sustainable cultivated landscapes in Germany: Goals and requirements from an ecological, economic and legal perspective - Stefan Möckel; Marieke Baaken; Bartosz Bartkowski; Michael Beckmann; Elisabeth Henn; Michael Strauch; Jessica Stubenrauch (Helmholtz-Zentrum für Umweltforschung (UFZ), 2024)
The global increase in greenhouse gases is also changing the climate conditions more severely in Germany. This particularly affects local cultivated landscapes, which cover large parts of Germany and are already experiencing a wide range of ecological problems. Although agricultural land use characterises cultivated landscapes, their sustainability does not only depend on a change in farming methods. The creation of sustainable cultivated landscapes requires an approach that goes beyond individual actions, which is rather a task for society as a whole that extends well beyond the responsibility and possibilities of individual landowners and managers. Based on the common ecological problems and the specific challenges of climate change described in more detail in the article, we therefore analyse what sustainability means and which social goals and requirements can be identified for cultivated landscapes. The article aims to create a basis for developing practical concepts for measures, government regulations and state subsidies.
Keywords: 330; climate change; cultivated landscape; agriculture; forestry; sustainability; international law; European law; constitutional law; nature conservation; ecosystems; biodiversity